Comments on "increasing the natural frequencies of circular disks using internal channels" - Laura, Patricio Adolfo Antonio (2001)
An investigation on a novel design of computer disk drive disks that raises their natural frequencies was presented. Natural frequencies were raised by adequately subtracting mass from the structural element under consideration. This procedure was called dynamic stiffening. The dynamic stiffening efficiency factor was also defined. The dynamic stiffening efficiency factor could be extended to higher natural frequencies.